Implementation of personal health records by case managers in a VAMC general medicine clinic - Tobacman, Joanne K; Kissinger, Pamella; Wells, Marilyn; Prokuski, Joan; Hoyer, Mary; McPherson, Patricia; Wheeler, Julie; Kron-Chalupa, Joyce; Parsons, Carol; Weller, Patricia; Zimmerman, Bridget (Patient education and counseling, 2004)
The study objective was to determine the feasibility of implementation of personal health records (PHRs) by case managers (CMs) in a Veterans Affairs Medical Center (VAMC) Continuity of Care (COC) Clinic, to ascertain the impact of PHRs on patient access to vital health information, and to assess the effect on provider–patient communication. One hundred and fifty patients and 8 nurse CMs in the general medicine COC Clinic at the Iowa City VAMC participated in a prospective cohort study in which an intervention, implementation of PHRs, was performed in one half of the patients, selected at random by their CMs. All participants responded to questions about their personal possession of documentation of vital health information. Initially, the majority of subjects possessed poor documentation of basic health information. At follow-up, significant differences occurred between the cohort with PHRs and the cohort without in their documentation of immunizations, allergies, medications, and operations.